Incidence of severe adverse events in cancer patients after treatment with immune-checkpoint inhibitors during the COVID- 19 pandemic - Sakiko Kimura; Hiroo Katsuya; Chiho Nakashima; Naoko Sueoka-Aragane; Koji Hayashida; Kazumi Sasaki; Rintaro Sogawa; Tatsuya Furuno; Moriyasu Yamauchi; Yoichiro Sugiyama; Hirokazu Noshiro; Motohiro Esaki; et al. (BMC Immunology)
Abstract Immune-checkpoint inhibitors (ICIs) can cause inflammation and immune-related adverse events (irAEs). Although irAEs may be caused by dysregulation of cytokines, the impact of various COVID- 19-related factors on expression of ICI-related AEs remains unclear. Assessment of AEs following ICI administration during the COVID- 19 pandemic may provide valuable insights that enable optimization of patient selection, thereby maximizing the benefits of ICI therapy. The aim of this study was to investigate the actual occurrence of severe AEs after ICI administration during the COVID- 19 pandemic. The medical records of patients who received ICI at Saga University Hospital were examined retrospectively. The primary endpoint was the incidence of all AEs ≥ Grade 3 that occurred after ICI administration. The survey period, from Jan 2020 to Dec 2022, was divided into an earlier (Jan 2020–March 2021) and a later (April 2021–Dec 2022) period. AEs with a clear cause other than ICI were excluded from the analysis. A total of 527 patients were included in the analysis, with a median follow-up of 422 days. During the COVID- 19 pandemic, the incidence of AEs ≥ Grade 3 after ICI administration was 52.8%. The incidence of AEs ≥ Grade 3 AEs after ICI administration was significantly higher during the later period [23.4% (57/244) in the earlier period and 49.8% (236/474) in the later period; mixed effect model p < 0.0001, odds ratio, 3.37 (95% CI: 2.32–4.89)]. Overall survival was significantly worse in the group with AEs ≥ Grade 3 than in the group without AEs ≥ Grade 3 [HR (95% CI) = 0.48 (0.36–0.65), p = 0.0001]. During the COVID- 19 pandemic, it became clear that the incidence of severe AEs (including irAEs) increased after ICI administration, particularly during the later period of the disease. Various factors may be associated with occurrence of severe AEs after ICI administration, and long-term careful observation and prospective multicenter clinical studies are required.